Disulfide High‐Mobility Group Box 1 Drives Ischemia‐Reperfusion Injury in Human Liver Transplantation. Issue 3 (30th October 2020) - Sosa, Rebecca A.; Terry, Allyson Q.; Kaldas, Fady M.; Jin, Yi‐Ping; Rossetti, Maura; Ito, Takahiro; Li, Fang; Ahn, Richard S.; Naini, Bita V.; Groysberg, Victoria M.; Zheng, Ying; Aziz, Antony; et al.
Abstract : Background and Aims: Sterile inflammation is a major clinical concern during ischemia‐reperfusion injury (IRI) triggered by traumatic events, including stroke, myocardial infarction, and solid organ transplantation. Despite high‐mobility group box 1 (HMGB1) clearly being involved in sterile inflammation, its role is controversial because of a paucity of patient‐focused research. Approach and Results: Here, we examined the role of HMGB1 oxidation states in human IRI following liver transplantation. Portal blood immediately following allograft reperfusion (liver flush; LF) had increased total HMGB1, but only LF from patients with histopathological IRI had increased disulfide‐HMGB1 and induced Toll‐like receptor 4–dependent tumor necrosis factor alpha production by macrophages. Disulfide HMGB1 levels increased concomitantly with IRI severity. IRI + prereperfusion biopsies contained macrophages with hyperacetylated, lysosomal disulfide‐HMGB1 that increased postreperfusion at sites of injury, paralleling increased histone acetyltransferase general transcription factor IIIC subunit 4 and decreased histone deacetylase 5 expression. Purified disulfide‐HMGB1 or IRI + blood stimulated further production of disulfide‐HMGB1 and increased proinflammatory molecule and cytokine expression in macrophages through a positive feedback loop. Conclusions: These data identify disulfide‐HMGB1 as a mechanistic biomarker of, and therapeutic target for, minimizing sterile inflammation during human liver IRI.